Effects of lisdexamfetamine in a rat model of binge-eating - Vickers, Steven P; Hackett, David; Murray, Fraser; Hutson, Peter H; Heal, David J (Journal of psychopharmacology (Oxford), 2015)
Binge-eating disorder is a common psychiatric disorder affecting ~2% of adults. Binge-eating was initiated in freely-fed, lean, adult, female rats by giving unpredictable, intermittent access to ground, milk chocolate over four weeks. The rats avidly consumed chocolate during 2 hr binge sessions, with compensatory reductions of normal chow intake in these sessions and the days thereafter. Bodyweights of binge-eating rats were normal. The model's predictive validity was explored using nalmefene (0.1-1.0mg/kg), R-baclofen (1.0-10mg/kg) and SB-334867 (3.0-30 mg/kg) (orexin-1 antagonist), which all selectively decreased chocolate bingeing without reducing chow intake. Sibutramine (0.3-5.0mg/kg) non-selectively reduced chocolate and chow consumption. Olanzapine (0.3-3.0mg/kg) was without effect and rolipram (1.0-10mg/kg) abolished all ingestive behaviour. The pro-drug, lisdexamfetamine (LDX; 0.1-1.5mg/kg), dose-dependently reduced chocolate bingeing by ⩽ 71% without significantly decreasing normal chow intake. Its metabolite, D-amphetamine (0.1-1.0mg/kg), dose-dependently and preferentially decreased chocolate bingeing ⩽ 56%. Using selective antagonists to characterize LDX's actions revealed the reduction of chocolate bingeing was partially blocked by prazosin (α1-adrenoceptor; 0.3 and 1.0mg/kg) and possibly by SCH-23390 (D1; 0.1mg/kg). RX821002 (α2-adrenoceptor; 0.1 and 0.3mg/kg) and raclopride (D2; 0.3 and 0.5mg/kg) were without effect. The results indicate that LDX, via its metabolite, d-amphetamine, reduces chocolate bingeing, partly by indirect activation of α1-adrenoceptors and perhaps D1 receptors.